PEMBERDAYAAN PENGRAJIN PRODUK APEM DI DESA KADUBUNGBANG-CIMANUK-PANDEGLANG - Akhmad Nidhomuz Zaman; Santika Sari; Fitri Wahyuni; Noverdo Saputra (Jurnal Abdi Masyarakat, 2020)
ABSTRACTThe development of the industrial center area is one of the efforts to build a local economythat aims to construct commodity-based production of the village that is owned by the localcommunity. Community Service (PKM) is carried out in Kadubungbang-PandeglangVillage. PKM is done to assist in the empowerment of typical Pandeglang culinary businessin the home industry "Apem Bohay Barokah". The current problem is not yet maximized inapem marketing (in terms of packaging and sales that are still sold around the village).Marketing is assisted on the packaging side with contemporary packaging designs andmaking posters to be better known and known to the general public. PKM was accepted byApem Bohay Pandeglang's business. Marketing is not only done in terms of packagingproducts and banners but also assisted in terms of digitizing one of them with the androidapplication. It is hoped that this empowerment can be better known by the Pandeglangcommunity as well as expanding and establishing sustainable partnerships.Keywords: home industry, culinary, marketing, empowerment.ABSTRAKPembangunan kawasan sentra industri merupakan salah satu upaya untuk membangunperekonomian lokal yang bertujuan membangun produksi berbasis komoditas unggulanDesa yang dimiliki oleh masyarakat setempat. Pelaksanaan kegiatan Pengabdian KepadaMasyarakat (PKM) dilakukan di Desa Kadubungbang-Pandeglang. PKM yang dilakukanadalah membantu dalam pemberdayaan usaha kuliner khas pandeglang pada home industriâ€œApem Bohay Barokahâ€. Permasalahan saat ini adalah belum maksimal pada pemasaranapem (dari sisi pengemasan dan penjualan yang masih di jual disekitar Desa). Pemasaran dibantu pada sisi pengemasan dengan desain pengemasan yang kekinian serta membuat posteruntuk lebih dikenal dan diketahui khalayak umum. PKM diterima pihak usaha Apem BohayPandeglang. Pemasaran tidak hanya dilakukan dari sisi pengemasan produk dan spanduktetapi juga dibantu dari sisi digitalisasi salah satunya dengan aplikasi android. Diharapkanpemberdayaan ini bisa lebih di kenal masyarakat Pandeglang serta meluas dan terjalinkemitraan yang bekelanjutan.Kata kunci: home industri, kuliner, pemasaran, pemberdayaan